Blood pressure and proteinuria control remains a challenge in patients with type 2 diabetes mellitus and chronic kidney disease: experience from the prospective observational ALICE-PROTECT study. Issue 1 (December 2016) - Halimi, Jean-Michel; Joly, Dominique; Combe, Christian; Choukroun, Gabriel; Dussol, Bertrand; Fauvel, Jean-Pierre; Quéré, Stéphane; Fiquet, Béatrice
Abstract Background Type 2 diabetes (T2DM) is the leading cause of chronic kidney disease (CKD) in western countries. The combination of both increases the risk of end stage renal disease (ESRD), cardiovascular events and all-cause mortality. Early control of blood pressure (BP) and proteinuria (Pu) is crucial to slow down the progression of the CKD and prevent cardiovascular events and mortality. The primary objective of the study was to assess BP and Pu control after a 2-year follow-up in T2DM patients with CKD. Methods Prospective, multicenter, observational study. Overall, 153 French nephrologists included 986 T2DM patients with Pu (≥0.5 g/day) and an eGFR >15 ml/min/1.73 m2 . Data from 729 patients were available after a 2-year follow-up. BP and Pu control were respectively defined as less than 140/90 mmHg and 0.5 g/day. We also looked at renal and cardiovascular events. Results At baseline, 74 % of the patients were male, mean age was 70 years. The mean T2DM duration was 17 years with a mean HbA1c of 7.4 %. All were treated for hypertension and 33 % had a controlled BP; 81 % had dyslipidemia and LDLc was <1 g/L for 54 %; 44 % had retinopathy, 40 % macrovascular complications and 12 % heart failure. Mean Pu was 2 g/day and eGFR 40 ± 20 mL/min/1.73 m2, with 13, 18, 32 and 37 % of the patients in respectively stage 2, 3a, 3b and 4 CKD. After two years, 21 % reached the Pu target and 39 % the BP target. The mean eGFR of 40 ± 20.3 ml/min/1.73 m2 at baseline dropped to 33.9 ± 22.6 ml/min/1.73 m2 by year two (p < 0.001). This corresponded to a mean annual eGFR reduction of 3.2 ml/min/1.73 m2 . 118 patients presented a renal event (16.2 %): doubling of serum creatinine for 86 patients (11.8 %) and start of dialysis for 72 (9.9 %); 176 patients (24.1 %) developed at least one cardiovascular complication (mainly coronary events and acute heart failure) during the follow-up period, and among these, 50 had also developed renal complications. Sixty patients died, i.e., 8.2 %, 26 patients from cardiovascular causes. Conclusion Our study highlights that achieving BP and Pu targets remains a major challenge in patients with T2DM and nephropathy. Renal failure emerges as a more frequent event than death.